2014
DOI: 10.1159/000365987
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Intestinal Lymphangiectasia with Protein-Losing Enteropathy: White Villi Type and Non-White Villi Type

Abstract: Background/Aims: We classified intestinal lymphangiectasia (IL) into two categories, the white and non-white villi types, and evaluated their clinical characteristics and therapeutic responses. Methods: Of the 988 patients who underwent double-balloon enteroscopy, 14 consecutive patients (7 men and 7 women, median age at onset 34 years) were enrolled with immunohistochemically confirmed IL with protein-losing enteropathy. Results: Enteroscopically the white villi type (n = 8) showed white plaques and white-tip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…We proposed a classification of intestinal lymphangiectasia into white villi type (the former lamina propria dominant type) and non-white villi type (the latter deeper layer dominant type) according to the enteroscopic findings, which clustered its manifestations and severity. Enteroscopically, the non-white villi type showed that apparently normal, but under more detailed observation, low and round villi with a normal color, were diffused 17 . In two of three patients with non-white villi type intestinal lymphangiectasia, pCLE was able to detect lymphangiectasia, while detection did not occur in the remaining patient who was diagnosed only by autopsy, showing predominantly subserosal lymphangiectasia accompanied by marked fibrosis in the submucosal layer (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…We proposed a classification of intestinal lymphangiectasia into white villi type (the former lamina propria dominant type) and non-white villi type (the latter deeper layer dominant type) according to the enteroscopic findings, which clustered its manifestations and severity. Enteroscopically, the non-white villi type showed that apparently normal, but under more detailed observation, low and round villi with a normal color, were diffused 17 . In two of three patients with non-white villi type intestinal lymphangiectasia, pCLE was able to detect lymphangiectasia, while detection did not occur in the remaining patient who was diagnosed only by autopsy, showing predominantly subserosal lymphangiectasia accompanied by marked fibrosis in the submucosal layer (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…Ohmiya et al noted that the white villi type (white plaques and white-tipped villi) as reflecting the pathological feature of dilated lymphatic vessels in the lamina propria, while the non-white villi type represented the dilation of the lymphatic vessels in the submucosal layer or deeper (5). In our study, Patient 2 had similar white villi, confirming the dilation of the lymphatic vessels in the lamina propria.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, the variable course of PLE in the natural history of PIL is not unique for CHAPLE patients. Some of the reported PIL cases had spontaneous recovery of their symptoms, remaining well for prolonged period, with relapses over time …”
Section: Chaple Disease: a Familial Form Of Isolated Pil Variably Asmentioning
confidence: 97%
“…Individual reports have described thrombotic events among patients with PLE caused by various etiologies, including PIL, PLVAP deficiency, and lupus‐related enteropathy . Among several predisposing factors, the theory that loss of anti‐coagulatory molecules such as anti‐thrombin III, protein C, protein S, and plasminogen in the gut produces a thrombophilic state in PLE has gained specific interest .…”
Section: Chaple Disease: a Familial Form Of Isolated Pil Variably Asmentioning
confidence: 99%
See 1 more Smart Citation